2014
DOI: 10.1103/physreva.89.013836
|View full text |Cite
|
Sign up to set email alerts
|

Structure of molecular packing probed by polarization-resolved nonlinear four-wave mixing and coherent anti-Stokes Raman-scattering microscopy

Abstract: International audienceWe report a method that is able to provide refined structural information on molecular packing in biomolecular assemblies using polarization-resolved four-wavemixing and coherent anti-Stokes Raman-scattering microscopy. These third-order nonlinear processes allow quantifying high orders of symmetry which are exploited here to reveal a high level of detail in the angular disorder behavior at the molecular scale in lipid membranes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(86 citation statements)
references
References 26 publications
5
81
0
Order By: Relevance
“…In particular, S 2 is equal to 0 in isotropic samples, and increases with increasing order, e.g., decreasing width of the molecular angular distribution excited in the focal volume. Note that the relation between the obtained S 2 ; φ 2 parameters and the intrinsic molecular order taking place within the focal spot of the microscope can be directly related to regular polarization-resolved CARS and SRS [17]. In particular, it can be shown that when the polarization dependence of the measured intensity is truncated to its second-order Fourier series such as done in Eq.…”
Section: Principle Of Fast-polarization Crs Imagingmentioning
confidence: 95%
See 4 more Smart Citations
“…In particular, S 2 is equal to 0 in isotropic samples, and increases with increasing order, e.g., decreasing width of the molecular angular distribution excited in the focal volume. Note that the relation between the obtained S 2 ; φ 2 parameters and the intrinsic molecular order taking place within the focal spot of the microscope can be directly related to regular polarization-resolved CARS and SRS [17]. In particular, it can be shown that when the polarization dependence of the measured intensity is truncated to its second-order Fourier series such as done in Eq.…”
Section: Principle Of Fast-polarization Crs Imagingmentioning
confidence: 95%
“…Here we do not represent higher harmonics that could be treated as additional information [17]. S 2 and φ 2 are, respectively, related to the degree of alignment of molecular bonds within the focal spot of the microscope objective and to its average orientation (see Supplement 1).…”
Section: Principle Of Fast-polarization Crs Imagingmentioning
confidence: 99%
See 3 more Smart Citations